On the problem of improving the physical abilities of the younger generation - V.P. Ivaschenko; V.O. Pustovalov; O.O. Bezkopulnuy; V.O. Suprunovich; S.V. Grechukha (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: identify ways to improve the physical capabilities of children, school children, teenagers and young people enrolled in educational institutions. Material : analysis and synthesis of 22 references for the improvement of the physical capabilities of the younger generation. Results: found that physical education is an integral and very important part of preparing students for life. Physical education class in secondary schools in any case not be turned into a form of entertainment with elements of locomotors activity. Meeting the challenges of physical education should be on the leading position, especially in working with younger students. In the process of improving the physical abilities of students, physical education teacher must always remember that the most spectacular method of education is a personal example of a teacher. Conclusions : optimization studies are actual educational process considering the personal qualities of the expert.